Analisis Letak Tracking Di Area Arteri Carotis Interna Dan Arcus Aorta Pada Pemeriksaan Cta Cerebral Di Instalasi Radiologi RSUD Salatiga - Widya Mufida (Poltekkes Kemenkes Semarang, 2022)
Background: In the CTA examination of cerebral angiography at the Radiology Installation of Salatiga Hospital, the flow rate used was 5 ml/s, bolus tracking contrast media was placed in 2 different places, some radiographers used the internal carotid artery and some used the aortic arch as an indicator of ROI tracking. Image acquisition is done by adjusting the scan delay post injection of contrast media and pre bolus tracking, so that the difference in the placement of the tracking affects the scan delay time and the dose given to the patient. The purpose of this study is to determine the location of accurate tracking in terms of image information and radiation dose given to the patient.Methods: This type of research is descriptive with qualitative data. The research object is the patient who performs Cerebral CTA examination with tracking location on the interna carotid artery(ICA) and aortic arch. The research subjects were 2 radiographers and 1 radiologist. Data collection was done by interview observation method.Results: Research shows that in Cerebral CTA examination using ROI tracking in the ICA area, there is a risk of contrast media entering the blood vessels if the scan delay time setting is not right, while the ROI tracking setting in the aortic arch is safer if the patient moves the tracking location is still around blood vessels but the radiation given to the patient tends to be larger as the scanning area increasesConclusions: The use of tracking ROI in the area of the internal carotid artery and aortic arch on CTA Cerebral examination can be used according to the radiographer's expertise in finding these blood vessels, the use of the right scan delay time affects the scanning results produced.